DEVELOPMENT OF TUTORIAL VIDEO FOR PALM OIL WASTE TREATMENT IN THE SUBJECT OF WORKSHOP AND ENTREPRENEURSHIP - Muhammad Arista Ramadhani; Adlim Adlim; Latifah Hanum (Chimica Didactica Acta, 2020)
This study aims to develop, to analyze the feasibility, and to describe students' responses to the video tutorial learning media using the Sony Vegas Pro 13 software on palm oil waste processing material in the Craft material d. This type of research is research and development (Research and Development / RD). The video tutorial learning media developed in this study is the ADDIE model which has five stages, namely, (1) analysis, (2) design, (3) development (4) Implementation and (5 ) Evaluation. Data collection was carried out at SMA Negeri 1 Sampoiniet with 20 students taken from class X. The feasibility of video tutorial media was assessed by Experts at 93.18% and student responses to the video tutorial media developed were 91.8% each with a very good category. Based on the results of the study, it can be concluded that the video tutorial media developed is very suitable for use in the learning process of waste treatment materials.